When Agility Meets a Project Portfolio: A Study of Success Factors in Large Organisations - Aghajani, Masoud; Ahsan, Kamrul; Whiteside , Naomi (Australasian Journal of Information Systems, 2023)
The iterative nature of agile methods combined with high levels of team and customer interactions and continuously changing IT and software development project requirements make the management of agile project portfolios very complex. To date, the mechanisms under which project portfolio management adapts to these complexities and achieves portfolio success have not been thoroughly investigated. This study explores the notion of success and its impacting factors in large organisations’ portfolios of agile IT and software development projects. Using a multiple case study design, we analysed the agile project portfolios of seven large organisations. We identified four success criteria and 15 success factors and categorised them into a unique agile portfolio success framework. Some of these criteria and factors are unique to agile project portfolios. The framework contributes to agile and project management literature by conceptualising the notion of success in portfolios of agile projects while revealing a set of factors that affect the relationship between an agile portfolio with its subcomponents and the surrounding environment. The framework supports managers and practitioners in large organisations in reflecting on their agility efforts to achieve higher success rates in their agile portfolios.